Optimizing earning quality in bank finance: a theoretical model and empirical investigation in India - Ketan Mulchandani; Santanu K. Ganguli; Kalyani Mulchandani (Cogent Economics & Finance)
Agency theory highlights that debt serves as a tool to monitor managerial behaviour of the borrowing firms. We argue that in a privately negotiated banking system, the monitoring should encompass the earning quality of the firms. Accordingly, the paper develops a theoretical model that shows an inverted U-shaped relationship between earning quality and bank finance, implying an ‘optimum earning quality’ that maximises the benefit of the monitoring role of bank finance. The empirical results based on a sample of 1511 firm-years support the model and imply that the bankers’ monitoring must be adequate to encompass earning quality to generate benefit to cover cost of the latter at higher level of debt. Shortcoming of supervision means earning quality being compromised that leads to higher credit risk for the bankers. The bankers seem to rely more on collaterals over earning quality for credit risk mitigation. This finding aligns with the objective of the study which highlights a need for incorporating more robust mechanisms to evaluate earning quality of the borrowers. Therefore, the bankers’ monitoring must cover quality of earning of the borrowers more rigorously at higher level of debt.